PENGEMBANGAN E-MODULE BERBASIS REPRESENTASI KIMIA PADA MATERI KESETIMBANGAN ION DALAM LARUTAN GARAM UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Annida Nurul Shabrina; Salastri Rohiat; Rina Elvia (ALOTROP, 2023)
This study aims to help students understand the ion balance material in a salt solution more easily at the three levels of chemical representation, by developing an e-module. E-module was developed using Flip PDF Professional with ADDIE development model. The research was conducted at SMA Negeri 3 Bengkulu City with a research sample of 12 students of class XI MIPA 5 for small-scale trials and 28 students of class XI MIPA 3 for large-scale trials. The research data were obtained from interviews, material and media validation questionnaires, student response questionnaires, and e- module readability, as well as pretest and posttest results. The results of the study obtained that the feasibility level of the e-module on the material aspect was 90% and the media was 95.45% with both categories being very valid. Student responses obtained percentage results, namely 86.11% with very good criteria, and e-module readability for students, namely 87.38% in the very readable category. The N-Gain score for students' cognitive learning outcomes at 0.812 which was included in the high category. The results of this study indicate that the e-module based on the chemical representation of the ion balance material in a salt solution is very good and suitable for use in the learning process because it helps students understand the material at three levels of chemical representation, namely macroscopic, submicroscopic and symbolic. Keywords: e-module, representation, chemical